Pharmacogenetic Sex-Specific Effects of Methotrexate Response in Patients with Rheumatoid Arthritis - Francisco C. Ceballos; Eugenio Chamizo-Carmona; Carmen Mata-Martín; Carmen Carrasco-Cubero; Juan J. Aznar-Sánchez; Raúl Veroz-González; Sara Rojas-Herrera; Pedro Dorado; Adrián LLerena (MDPI AG, 2023)
Methotrexate (MTX) is a commonly used drug for the treatment of rheumatoid arthritis (RA), but its effectiveness can vary greatly among patients. Pharmacogenetics, the study of how genetic variations can affect drug response, has the potential to improve the personalized treatment of RA by identifying genetic markers that can predict a patient's response to MTX. However, the field of MTX pharmacogenetics is still in its early stages and there is a lack of consistency among studies. This study aimed to identify genetic markers associated with MTX efficacy and toxicity in a large sample of RA patients, and to investigate the role of clinical covariates and sex-specific effects. Our results have identified an association of ITPA rs1127354 and ABCB1 rs1045642 with response to MTX, polymorphisms of FPGS rs1544105, GGH rs1800909, and MTHFR genes with disease remission, GGH rs1800909 and MTHFR rs1801131 polymorphisms with all adverse events, and ADA rs244076 and MTHFR rs1801131 and rs1801133, However, clinical covariates were more important factors to consider when building predictive models. These findings highlight the potential of pharmacogenetics to improve personalized treatment of RA, but also emphasize the need for further research to fully understand the complex mechanisms involved.